Evaluation of autonomic imbalance in irritable bowel syndrome and functional dyspepsia - D’Souza, Leroy; Chikkaiah, Prakash Banahalli; K. S., Prashanth; Singhvi, Maanini (Rzeszów University Press, 2026)
Introduction and Aim. Irritable bowel syndrome (IBS) and functional dyspepsia (FD) are functional gastrointestinal disorders that may involve autonomic imbalance. This study assessed autonomic nervous system activity using short-term heart rate variability (HRV). To our knowledge, this is the first study in an Indian population to directly compare autonomic modulation across IBS subtypes and FD using a unified HRV protocol, demonstrating subtype-specific alterations ‒ particularly reduced LF/HF in IBS-diarrhea (IBS-D). Material and methods. Thirty IBS patients and thirty FD patients diagnosed using the Rome IV criteria, along with thirty healthy controls, were enrolled. Short-term HRV analysis was performed following ECG acquisition using the LABCHART platform. Results. Mean low-frequency/high-frequency (LF/HF) ratio was 1.26±0.83 in IBS, 1.40±1.171 in FD, and 1.60±1.196 in controls. High-frequency (HF) power values (ms²) were 733.9±1661.16 (IBS), 534.18±778.28 (FD), and 674.87±1187.16 (controls), with no significant differences among the three groups (p>0.05). Subgroup analysis revealed significantly lower LF/HF values in IBS-D compared to controls (0.98±0.69 vs. 1.60±1.196; p=0.038), while HF values did not differ (p>0.05). No significant differences were found between IBS-constipation (IBS-C) patients and controls. Conclusion. IBS-D patients exhibited decreased LF/HF and increased HF values, indicating enhanced parasympathetic modulation, which may contribute to diarrhea-predominant symptoms. IBS-C patients showed a trend toward higher LF/HF and lower HF values, compatible with increased sympathetic modulation, although results were not statistically significant. FD patients showed no autonomic differences relative to controls. These findings highlight subtype-specific autonomic patterns in IBS and provide novel HRV-based insights from an Indian cohort.
The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved on 16/6/2023 by the BMCRI Institutional Ethics Committee, Bangalore Medical College and Research Institute, Bangalore (No: BMCRI/PS/85/2022-23).
Keywords: autonomic imbalance; autonomic nervous system; constipation; dyspepsia; gastrointestinal diseases; irritable bowel syndrome